PENGEMBANGAN GAME KAHOOT SEBAGAI MEDIA EVALUASI HASIL BELAJAR SISWA - ARIEF MASYRUFIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The increasingly rapid development of technology can be used as an innovation that can support optimization in the evaluation of effective learning, because technology offers various kinds of convenience in it. Utilization and use of technology in the learning process is able to maximize student learning activities. One form of utilizing technological advances in education is the Kahoot learning application. The development model used by the researcher is the 4D model, formed from 4 main stages such as: define, design, development, and disseminate. The results of the validation by material experts obtained a percentage of 80%